2003
DOI: 10.1167/iovs.02-0913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold-Induced Vasospasm in Glaucoma: The Role of Endothelin-1

Abstract: Patients with glaucoma have an abnormal increase in plasma ET-1 after the body cools. It is possible that at least in some patients, increased levels of ET-1 in response to vasospastic stimuli may be involved in the pathogenesis of glaucomatous damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 40 publications
3
86
1
4
Order By: Relevance
“…Kunimatsu et al [25] found a higher ET-1 plasma level in patients with POAG as compared to the control group (1.33 § 0.50 pg/mL), but with no statistical significance, unlike our results (Table 4). In 1997, Tezel et al [14] and, in 2003, Nicolela et al [9] also did not find significant differences in the EG-1 plasma concentration between healthy and POAG patients as well (Table 4). …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Kunimatsu et al [25] found a higher ET-1 plasma level in patients with POAG as compared to the control group (1.33 § 0.50 pg/mL), but with no statistical significance, unlike our results (Table 4). In 1997, Tezel et al [14] and, in 2003, Nicolela et al [9] also did not find significant differences in the EG-1 plasma concentration between healthy and POAG patients as well (Table 4). …”
Section: Resultsmentioning
confidence: 89%
“…Increased levels of ET-1 are found in acute renal failure, hypertension, heart failure, ischemic heart disease, Prinzmetal angina, pulmonary hypertension, Raynaud's disease, subarachnoid hemorrhage, cerebral vasospasm, migraine and diabetes [5,9]. EG-1 is normally found in the eye, where it is produced by the non-pigmented ciliary epithelium and is released into the intraocular liquid [10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies demonstrated that patients with glaucoma, in contrast to the control subjects, have an abnormal hyperactivity of ET-1 in response to vasospastic stimuli such as cold. 58 It has been postulated that an imbalance between vasoconstrictor substances such as 59,60 It was reported that patients with glaucoma who have vasospasm have a higher susceptibility to glaucomatous damage, which could be a consequence of a decreased dilation of blood vessels that properly autoregulate blood flow. 55 If our speculation is correct, BCACs induce normalization of ET-1, and its receptor balance may be beneficial for ocular blood circulation, since an increased ET-1 reactivity could lead to decreased ocular blood flow as indicated above.…”
Section: Discussionmentioning
confidence: 99%
“…33,[40][41][42][43] These apparent alterations in the circulation of the glaucomatous optic nerve may implicate dysfunction of vascular regulatory mechanisms. Further support for vascular dysregulation has been suggested by the finding of elevation of ET-1, a potent vasoconstricting peptide, in the plasma 39,[44][45][46] and aqueous humor 47,48 of patients with glaucoma. In the optic nerve, evidence of decreased blood flow correlating with visual field damage has been reported in glaucoma patients.…”
Section: Glaucoma and Systemic Vascular Diseasementioning
confidence: 98%